2021
DOI: 10.1111/1365-2435.13830
|View full text |Cite
|
Sign up to set email alerts
|

Counter‐gradient variation of reproductive effort in a widely distributed temperate oak

Abstract: The genetic and phenotypic variability of life‐history traits determines the demographic attributes of tree populations and, thus, their responses to anthropogenic climate change. Growth‐ and survival‐related traits have been widely studied in forest ecology, but little is known about the determinism of reproductive traits. Using an elevation gradient experiment in the Pyrenees, we assessed the degree to which variations in reproductive effort along climatic gradients are environmentally or genetically driven,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…4 ). It should be also noticed that our results are also in accordance with those of [ 79 ]. Indeed, these authors reported that at low elevation natural selection favors vegetative growth than reproduction thus explaining the early flushing date observed at low elevation.…”
Section: Discussionsupporting
confidence: 93%
“…4 ). It should be also noticed that our results are also in accordance with those of [ 79 ]. Indeed, these authors reported that at low elevation natural selection favors vegetative growth than reproduction thus explaining the early flushing date observed at low elevation.…”
Section: Discussionsupporting
confidence: 93%
“…Trade-offs between traits are common ecological and evolutionary phenomenon in nature, as they ensure the best use of outside resources . Trait trade-offs are particularly common in plants and sessile marine ectotherms because these types of organisms cannot shift their locality to avoid environmental variation (Karasov et al, 2017;Zust and Agrawal, 2017;Chauvin et al, 2018;Min et al, 2018;Caignard et al, 2021). Plenty of studies demonstrated that the trade-offs between reproduction, growth, and survival are the key forces that structure life-history variation (Culina et al, 2019;Cohen et al, 2020;Roach and Smith, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, to cope with environmental changes along an elevational gradient, plants in natural forests and plantings can adjust morphologically and physiologically, reducing LA, SLA, and increasing leaf thickness at higher elevations (Velázquez‐Rosas et al, 2002; Umaña and Swenson, 2019). Studies on functional traits and elevational gradients also indicate that intraspecific variability may result from phenotypic plasticity or genetic diversity (Conover and Schultz, 1995; Caignard et al, 2021). Some studies in plants on the extent of trait variation driven by environmental and/or genetic factors have provided evidence of countergradient variation where genetic and environmental effects are in opposite directions (Caignard et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Studies on functional traits and elevational gradients also indicate that intraspecific variability may result from phenotypic plasticity or genetic diversity (Conover and Schultz, 1995; Caignard et al, 2021). Some studies in plants on the extent of trait variation driven by environmental and/or genetic factors have provided evidence of countergradient variation where genetic and environmental effects are in opposite directions (Caignard et al, 2021). Also, the lack of variation in some traits across gradients may be due to constraints or countergradients that maintain phenotypes across the environment (Umaña and Swenson, 2019).…”
Section: Figurementioning
confidence: 99%